Combat narratives: the Aleutians campaign, June 1942 – August 1943. - Publications Branch, Office of Naval Intelligence, U.S. Navy (Washington, D.C. : Navy Department, Office of Naval Intelligence, 1945)
Combat Narratives have been prepared by the Publications Branch of the Office of Naval Intelligence for the information of the officers of the United States Navy. Contents: the attack on Dutch Harbor, June 1942; enemy occupation of Attu and Kiska; "strong attrition"- Kiska bombarded; occupation of Adak, 30 August 1942; occupation of Amchitka; first and second bombardment of Attu; destruction of enemy ammunition ship; the battle of the Komandorskis; invasion of Attu; softening up Kiska and the invasion of Kiska; and appendixes on task organization for the assault on Kiska, symbols of U.S. Navy ships, and list of published combat narratives.